Magnetic biomonitoring as a tool for assessment of air pollution patterns in a tropical valley using Tillandsia sp. - Mejía-Echeverry, Daniela (2018)
Recently, air pollution alerts were issued in the Metropolitan Area of Aburrá Valley (AVMA) due to the highest recorded levels of particulate matter (PM2.5 and PM10) ever measured. We propose a novel methodology based on magnetic parameters and an epiphytic biomonitor of air pollution in order to improve the air pollution monitoring network at low cost. This methodology relies on environmental magnetism along with chemical methods on 185 Tillandsia recurvata specimens collected along the valley (290 km2). The highest magnetic particle concentrations were found at the bottom of the valley, where most human activities are concentrated. Mass-specific magnetic susceptibility (χ) reaches mean (and s.d.) values of 93.5 (81.0) and 100.8 (64.9) × 10-8 m3 kg-1 in areas with high vehicular traffic and industrial activity, while lower χ values of 27.3 (21.0) × 10-8 m3 kg-1 were found at residential areas. Most magnetite particles are breathable in size (0.2-5 μm), and can host potentially toxic elements. The calculated pollution load index (PLI, based on potentially toxic elements) shows significant correlations with the concentration-dependent magnetic parameters (R = 0.88-0.93; p < 0.01), allowing us to validate the magnetic biomonitoring methodology in high-precipitation tropical cities and identify the most polluted areas in the AVMA.